(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In the twenty-first century, public policy extends beyond mere political action; it has evolved into a comprehensive process aimed at addressing and mitigating citizens' skepticism and negative attitudes toward the government. Rather than solely focusing on maximizing the happiness of the greatest number of people, contemporary public policy strives to minimize harm and uncertainty while striving to achieve the common good in the most effective manner possible. To achieve these objectives, public policy relies on a robust framework that incorporates insights from social, economic, and political disciplines. This interdisciplinary approach reflects a significant shift from traditional views of 'goodness' and acknowledges the complex social contexts within which policies are developed.